Creating academic economics in Brazil: The Ford Foundation and the beginnings of ANPEC - Ramón García Fernández; Carlos Eduardo Suprinyak (EconomiA, 2018)
The development of academic economics in Brazil received a major boost during the 1960s, when US institutions such as USAID and the Ford Foundation began to fund the first graduate programs in the field. An important moment occurred in 1973 with the creation of ANPEC, the national association responsible for promoting institutional interaction among the fledgling research centers. The paper explores material from the period 1964-74 held at the Ford Foundation archives, shedding some light on the conflicting motivations behind the creation of ANPEC, and indicating how the association affected the future course of the economics profession in Brazil.
Keywords: 330; ANPEC; Ford Foundation; Getúlio Vargas Foundation; University of S\~ao Paulo; USAID